PREMENOPAUSAL COUNSELING FLIPCHARTS AND ANXIETY LEVELS: A STUDY AT POSBINDU KARTINI, TIGARAKSA DISTRICT, AUGUST 2025 - Dafina Rahmawati; Nana, Dwi Ratna; Anah Sugihanawati; Entin Sutrini (Journal for Quality in Women's Health, 2026)
The research method employed a quasi-experimental design with a one-group pretest-posttest approach. The research population consisted of 70 premenopausal women aged 40-49 years, with samples collected using accidental sampling based on inclusion criteria. Data were gathered through demographic questionnaires, premenopausal knowledge assessments, and anxiety level measurements using the Hamilton Anxiety Rating Scale (HARS) before and after the counseling intervention. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. Results from 34 respondents showed that most respondents had insufficient knowledge (67.6%) and nearly half experienced severe anxiety (47.1%). Bivariate analysis showed a significant correlation between knowledge levels and anxiety (p=0.011). Counseling using flipchart media was effective in increasing knowledge (p=0.013). In conclusion, there is a significant correlation between knowledge and anxiety levels among premenopausal women, and premenopausal reproductive health counseling flipcharts are effective in increasing knowledge and reducing the levels of anxiety experienced during this transition period.